A Possible Role for Exocytosis in Aflatoxin Export in Aspergillus parasiticus - Chanda, Anindya (American Society for Microbiology, 2010)

(untitled)
Filamentous fungi synthesize bioactive secondary metabolites with major human health and economic impacts. Little is known about the mechanisms that mediate the export of these metabolites to the cell exterior. Aspergillus parasiticus synthesizes aflatoxin, a secondary metabolite that is one of the most potent naturally occurring carcinogens known. We previously demonstrated that aflatoxin is synthesized and compartmentalized in specialized vesicles called aflatoxisomes and that these subcellular organelles also play a role in the export process. In the current study, we tested the hypothesis that aflatoxisomes fuse with the cytoplasmic membrane to facilitate the release of aflatoxin into the growth environment. Microscopic analysis of A. parasiticus grown under aflatoxin-inducing and non-aflatoxin-inducing conditions generated several lines of experimental evidence that supported the hypothesis. On the basis of the evidence, we propose that export of the mycotoxin aflatoxin in Aspergillus parasiticus occurs by exocytosis, and we present a model to illustrate this export mechanism.